Ru(II)/clotrimazole/diphenylphosphine/bipyridine complexes: Interaction with DNA, BSA and biological potential against tumor cell lines and Mycobacterium tuberculosis - Colina-Vegas, Legna; Dutra, Jocely Lucena; Villarreal, Wilmer; de A. Neto, João Honorato; Cominetti, Marcia Regina; Pavan, Fernando [UNESP]; Navarro, Maribel; Batista, Alzir A. (Elsevier, 2016)
Three ruthenium complexes [RuCl(CTZ)(bipy)(P-P)]PF6 [P-P = 1,2-bis(diphenylphosphino)ethane (dppe-1), 1,4-bis(diphenylphosphino)butane (dppb-2) and 1,1′-bis(diphenylphosphino)ferrocene (dppf-3), bipy = 2,2′-bipiridine and clotrimazole (CTZ) 1-[(2-chlorophenyl)diphenylmethyl]-1H-imidazole] were synthesized. These complexes were characterized by a combination of elemental analysis, molar conductivity, infrared and UV–vis spectroscopy, 1H, 13C{1H} and 31P{1H} nuclear magnetic resonance techniques, cyclic voltammetry and mass spectroscopy. Bovine serum albumin binding constants, which were in the range of 1.30–36.00 × 104 M− 1, and thermodynamic parameters suggest spontaneous interactions with this protein by electrostatic forces due to the positive charge of the complexes. DNA interactions studied by spectroscopic titration, viscosity measurements, gel electrophoresis, circular dichroism, ethidium bromide displacement and reactions with guanosine and guanosine monophosphate indicated the DNA binding affinity primarily through non-covalent interactions. All complexes 1–3 were tested against the human carcinoma cell lines MCF-7 (breast), A549 (lung) and DU-145 (prostate) presenting promising IC50 values, between 0.50 and 14.00 μM, in some cases lower than the IC50 for the reference drug (cisplatin). The antimicrobial activity assays of the complexes provided evidence that they are potential agents against mycobacterial infections, specifically against Mycobacterium tuberculosis H37Rv.
Keywords: Antitumor and anti-Mycobacterium tuberculosis; Clotrimazole; Ruthenium-bisdiphenylphosphine